Exceptional preservation of nonmineralized biomaterials in Cenozoic fossils of the Mammalia clade (Research, Society and Development, 2022)
The members of the Mammalia class experienced high ecological, morphological and taxonomic diversification during the Cenozoic Era. With technological advances in molecular paleontology in recent decades, many claims for the exceptional preservation of nonmineralized biomaterials have been made for this clade. However, these data are scattered in the literature and have associated such reports with unique and rare events. This study presents a review of the literature published in the last six decades, aiming to investigate the frequency with which vestigial of nonmineralized biomaterials are found in Mammalia fossils. The results identified 79 published studies describing endogenous biocomponents in Metatheria and Theria members. Of these, protein fragments were more frequent in sedimentary deposits (33.3%), and ancient DNA sequences were more frequent in depositional environments more favorable to exceptional preservation (53.1%), such as ice and cave deposits. The data on organic material for mammalian fossils are geographically and taxonomically comprehensive, with the superordinates Laurasiatheria and Afrotheria presenting the largest number of reports. With the emergence and improvement of new techniques for the recovery of organic material, it is believed that paleomolecular information for fossil mammals should increase, in addition to broadening the understanding of taphonomic factors related to exceptional preservation.